Pengaruh Bermain Melukis Terhadap Kreativitas Anak Kelompok B Di Tk Pertiwi Dukuh 1 Mojolaban Sukoharjo Tahun Ajaran 2016/2017 - Rachmawati, Fibriyan; , Drs. Amrul Choiri, M.Ag (2017)
ABSTRACT The purpose of this study was to determine the influence of painting on the creativity of children playing in group B TK Pertiwi Dukuh 1 Mojolaban Sukoharjo, academic year 2016/2017. The method in this study is a quantitative method using a kind of experimental research with the research design (pre-experimental design). It used one group pretest-posttest design. This study was done on 14 children. The data collection techniques in this study conducted through participant observation and documentation. The data analysis techniques in this study used Ttest with SPSS 16.0 for Windows. The results of data analysis was Thitung value -6826 <= -Ttabel is -1.7709 then H0 rejected and Ha accepted which means that is a there are significant playing paint on children's creativity. Keywords: painting, creativity of children